Fast implementation of integer transforms in H.264/AVC video encoders - Lubobya, Smart Charles (Department of Electrical Engineering, 2015)
The Integer Discrete Cosine Transform (IDCT) and Hadamard transforms are adopted in the H.264/AVC standard encoder for the compression of residual video signals. Other video standards such as the H.261, H.262 and H.263 use Discrete Cosine Transform (DCT).